The influence of malocclusion, sucking habits and dental caries in the masticatory function of preschool children - Débora SOUTO-SOUZA; Maria Eliza Consolação SOARES; Ednele Fabyene PRIMO-MIRANDA; Luciano José PEREIRA; Maria Letícia RAMOS-JORGE; Joana RAMOS-JORGE (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract The aim of this study was to evaluate the association of malocclusion, nutritive and non-nutritive sucking habits and dental caries in the masticatory function of preschool children. A cross-sectional study was conducted with a sample of 384 children aged 3-5 years. A single examiner calibrated for oral clinical examinations performed all the evaluations (kappa > 0.82). Presence of malocclusion was recorded using Foster and Hamilton criteria. The number of masticatory units and of posterior teeth cavitated by dental caries was also recorded. The parents answered a questionnaire in the form of an interview, addressing questions about the child's nutritive and non-nutritive sucking habits. The masticatory function was evaluated using Optocal test material, and was based on the median particle size in the masticatory performance, on the swallowing threshold, and on the number of masticatory cycles during the swallowing threshold. Data analysis involved simple and multiple linear regression analyses, and the confidence level adopted was 95%. The sample consisted of 206 children in the malocclusion group and 178 in the non-malocclusion group. In the multiple regression analysis, the masticatory performance was associated with age (p = 0.025), bottle feeding (p = 0.004), presence of malocclusion (p = 0.048) and number of cavitated posterior teeth (p = 0.030). The swallowing threshold was associated with age (p = 0.025), bottle feeding (p = 0.001) and posterior malocclusion (p = 0.017). The number of masticatory cycles during the swallowing threshold was associated with the number of cavitated posterior teeth (p = 0.001). In conclusion, posterior malocclusion, bottle feeding and dental caries may interfere in the masticatory function of preschool children.